INTERNATIONAL NEWS AGENDA IN NATIONAL NEWSPAPERS AS A BASIS FOR PUBLIC UNDERSTANDING OF THE WORLD PICTURE - KurysYulia , Yulia; Potolokova, Maria; Nikonov, Sergey; Samsonova, Anastasiia; Kovalenko, Boris (Revista Inclusiones, 2020)
The article analyses the specifics of the international news agenda formed by national newspapers of different journalism cultures in the context of globalisation of information flow as one of the main factors of shaping the audience understanding of the surrounding world. One of the main questions is whether national newspapers having almost unlimited access to the worldwide news sources are able to provide the audience with sufficient information for understanding the world without inequalities and distortions. To answer this question the authors analyse geographical traits of the international news agenda for a national audience, explore cultural differences in the choice of news sources tactics in national newspapers, look for any possible connection between geographical gatekeeping features of international news coverage and foreign news sources used by newspapers. The research is based on the publications of three daily national newspapers of general interest belong to three different journalism cultures: British national version «The Guradian», Russian «Kommersant» and Spanish «ABC». Content Analysis includes a total of 3200 publications. The results make obvious that geographical spectrum of news agenda and news sources shows strong dependences while covering countries-leaders. Geographical picture of the world has significant shift to only one country-leader, characterized by limited spectrum of basic counties under coverage and includes a variety of countries-participants of the international news agenda